Cyberstalking Practices Among Youth in Türkiye: Motivational Drivers, Digital Avenues, and Perceptual Paradigms - Zindan Çakıcı (Türkiye İletişim Araştırmaları Dergisi)
Cyberstalking is a phenomenon that induces severe psychological disorders, including fear, anxiety,depression, and post-traumatic stress disorder, in victims. A critical synthesis of the literature identifiesa notable deficiency in multidimensional research concerning cyberstalking practices within the Turkishcontext. This study undertakes a comprehensive examination of cyberstalking practices among Turkishyouth, with a specific focus on the dynamics of inter-platform migration. Utilizing a snowball samplingtechnique, 16 participants aged 18-30, exhibiting diverse socio-demographic profiles, were recruited.During the experimental phase, participants engaged in a systematic and audible monitoring of anindividual, with whom they had either recently acquainted or had no prior information about, throughdigital media channels, replicating their routine cyberstalking practices. Subsequent semi-structuredinterviews were conducted to elicit detailed insights into participants’ cyberstalking practices. The findingsreveal Instagram as the primary locus of cyberstalking practices, driven by participants’ informationacquisition motives. X (Twitter) serves as a means to discern individuals’ political affiliations, Facebookas a repository of historical data, and Google facilitates access to individuals’ social networks. Notably,LinkedIn elicits the greatest participant unease due to notification mechanisms, while WhatsApp is leastutilized owing to data limitations. While participants generally perceive cyberstalking as normative, manyresort to various stratagems, including the creation of fictitious accounts, to access restricted profiles.Despite intensive engagement in these practices, the majority eschew self-identification as ‘stalkers,’ citingperceived excessiveness and intimidation associated with the label.